2022
DOI: 10.1039/d1gc04370f
|View full text |Cite
|
Sign up to set email alerts
|

Redox-active and Brønsted basic dual sites for photocatalytic activation of benzylic C–H bonds based on pyridinium derivatives

Abstract: A mild and efficient photocatalytic C-H bond activation strategy has been developed based on organic small molecule. A combination of excellent redox-active activity of pyridinium unit and Brønsted basic site...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“… , Two other DOM isolates, PPFA and ESHA with high aromaticities, also showed slight increases in carbonyl groups, as indicated by FTIR spectra (Figure S16 and Text S3). Meanwhile, the intensities of 1 H NMR spectra at 2.1 ppm, (i.e., the characteristic peak of R–CO–CH 3 ) , also increased in SO 4 •– -treated SRNOM samples compared to samples without SO 4 •– oxidation (Text S4 and Figure S17). Though the FTIR and NMR spectra can hardly be assigned to a specific group, the spectral changes can give some support on the transformation of alcohols to ketones in SRNOM upon SO 4 •– oxidation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“… , Two other DOM isolates, PPFA and ESHA with high aromaticities, also showed slight increases in carbonyl groups, as indicated by FTIR spectra (Figure S16 and Text S3). Meanwhile, the intensities of 1 H NMR spectra at 2.1 ppm, (i.e., the characteristic peak of R–CO–CH 3 ) , also increased in SO 4 •– -treated SRNOM samples compared to samples without SO 4 •– oxidation (Text S4 and Figure S17). Though the FTIR and NMR spectra can hardly be assigned to a specific group, the spectral changes can give some support on the transformation of alcohols to ketones in SRNOM upon SO 4 •– oxidation.…”
Section: Resultsmentioning
confidence: 97%
“…50,51 Two other DOM isolates, PPFA and ESHA with high aromaticities, also showed slight increases in carbonyl groups, as indicated by FTIR spectra (Figure S16 and Text S3). Meanwhile, the intensities of 1 H NMR spectra at 2.1 ppm, (i.e., the characteristic peak of R− CO−CH 3 ) 52,53 also increased in SO 4…”
Section: •−mentioning
confidence: 97%
“…More importantly, surface hydroxyl could get replenished by forming 1 O 2 ( • OH + • O 2 – → 1 O 2 + OH), which explained the stable performance of ZnSnAl-50 in the absolute dry condition. It was reported that 1 O 2 can effectively activate the C–H bond and had a relatively longer lifetime, contributing to the degradation of aromatic VOCs. , Therefore, the rapid ring-opening of aromatic VOCs over ZnSnAl-50 can be attributed to the synergy of rich surface hydroxyl and oxygen vacancies, enhancing reactant adsorption-activation and reactive oxygen species formation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The direct and selective oxidation of C–H bonds of organic compounds to corresponding high value-added chemicals, such as alcohols, ketones, and acids, holds great theoretical and practical significance. , Among them, the direct oxidation of benzyl C–H bonds is particularly important in heterogeneous catalysis, , such as the oxidation of ethylbenzene (EB) to produce acetophenone (AP), which is a key intermediate in the production of resins, fragrances, chewing gum, and drugs . However, the activation and cleavage of C–H bonds of EB typically require high-temperature initiation and catalyst excitation activation .…”
Section: Introductionmentioning
confidence: 99%